The effect of motivation on employee engagement in public sectors: Ein the case of North Wollo zone - Abriham Ebabu Engidaw (Journal of Innovation and Entrepreneurship, 2021)
The purpose of this study was to examine the effect of intrinsic and extrinsic motivation on employee engagement in public sectors. To meet this purpose, a quantitative and qualitative study survey was conducted and the researcher used an explanatory survey research design. The study was used both primary and secondary sources of data. The target population for this study was selected four city administrative office employees including all kebeles office employees and as a sample size, 349 questionnaires were filled and collected from these employees. The study used proportionately stratified with simple random sampling because to collect the relevant data and to give equal chance for all employees. Later on, statistical package for social science (SPSS) was used to the required test of inferential statistics; including reliability analysis, bivariate correlation, analysis of variance (ANOVA) test, and multiple regression analysis. The finding of the study revealed that extrinsic motivation was considered more significant than intrinsic and there was a positive significant relationship between intrinsic and extrinsic motivations with employee engagement. From the results, it was also concluded that the relationship and effect of extrinsic motivation were stronger on employee engagement as compared to intrinsic motivation. As a recommendation, the organizations should find which ways are able to motivate employees, what drives them, then making sure they utilize appropriate motivational techniques with each employee. Managers should also endeavor to communicate the organization's purpose to employees. Finally, the organizations should take steps to incorporate the vision of employees for the organization with its own vision.
Keywords: 650; Motivation; Intrinsic motivation; Extrinsic motivation; Employee engagement; Public sectors